Pembelajaran Bahasa Inggris dengan metode BCM di TK ABA V Temuguruh Kecamatan Sempu kabupaten Banyuwangi - Yayah Ikhda Nevia; Norita Citra; Muhammad Firman F; Tazkiyah Nur Aziza (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this service is to apply and describe developing English in children, especially for the ability to motivate themselves and establish social relationships through the BCM method (playing, telling stories and singing). This service is used to teach children so they can easily understand and memorize the vocabulary they are studying. Here children will get to know vocabulary such as fruits, numbers, professions, colors. And all this learning starts with stories and singing. Without realizing it, children will easily memorize it. In implementing the BCM method, children are expected to be serious but relaxed, remembering that children have limited concentration time and cannot be forced if the child is no longer able to concentrate.